Liquidity Management: A Multivariate Analysis of Financial Indicators of Two Steel Plants. (March 2015) - Mukherjee, Paroma Mitra; Roy, Dilip
Private and public organisations have experienced significant changes in recent years. To develop the core competencies greater skills are required in planning, analysis and control nowadays. This article develops a multivariate statistical model for the analysis to compare the short-term liquidity management of two giant steel companies in India. Durgapur Steel Plant (DSP; a sister plant of Steel Authority of India Ltd.) under public sector firm and Tata Steel plant as a whole is selected, which is the biggest private sector firm of India. Simultaneously, we have selected three financial ratios (current ratio (CR), inventory turnover ratio (ITR) and debtors turnover ratio (DTR)) describing liquidity position of a firm. These measures are interdependent and thus it can be considered to be a vector measure. Our objective is to verify whether the two sectors differ or not in respect of the mean vector measures. This hypothesis is examined with the help of Hotelling's T 2 —statistic under the assumption of equal dispersion. Significant differences have been observed in respect of liquidity position of these two firms. Along with that individual ratios have been checked for any significant difference or not for the said firms.